A Tale of the Tails: The Value of a Statistical Life at the Tails of the Age Distribution - Thomas J. Kniesner; W. Kip Viscusi (Institute of Labor Economics (IZA), 2024)
The considerable literature on the value of a statistical life (VSL) documents the wage-mortality risk tradeoffs for the working population. Regulatory analyses often must monetize risks to populations at the tails of the age distribution. Because of the longer life expectancy for children, there have been proposals to add a premium to their VSL, which would generate an inconsistency with revealed preference estimates of the VSL trajectory over the life cycle. The shorter life expectancy among older people has led to various arbitrary senior discounts for seniors' life expectancy. Application of the value of a statistical life year (VSLY) can address valuation of small changes in life expectancy. Examples of inappropriate age adjustments that we discuss include practices by the Consumer Product Safety Commission and the Environmental Protection Agency.
Keywords: J17; J28; I18; H40; K32; 330; circular A-4; Value of a Statistical Life; age; children; elderly; Value of a Statistical Life Year; VSL; VSLY